Applied fluid mechanics - Mott, Robert L. (Prentice Hall, 2000)
This popular applications-oriented approach to engineering technology fluid mechanics covers all of the basic principles of fluid mechanics--both statics and dynamics--in a clear, practical presentation that ties theory directly to real devices and systems used in chemical process industries, manufacturing, plant engineering, waste water handling and product design. "The Big Picture" sections--focus on real products or systems where the principles of fluid mechanics are used, discuss the kind of fluid used, what the fluid is used for, how it behaves, what conditions exist in the system that affect its behavior, and the relationships between those systems. Features a "programmed approach" to completely worked, complex, real-world example problems; spreadsheets; a unique presentation of the Moody diagram; highlighted major formulae and definitions; and an extensive set of appendix tables.